(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article examines the main directions for developing the institution of the marital contract in the Republic of Uzbekistan, taking into account current trends in family law and foreign experience. It reveals the concept and legal nature of the marital contract, analyses the specific features of its regulation under existing legislation, and explores the principal models of legal regulation in foreign legal systems. Specific proposals are formulated for improving the Family Code of the Republic of Uzbekistan in the part concerning the marital contract, including expanding the list of permissible terms, introducing electronic notarisation, and creating a unified register of marital contracts.